A New Lc-Ms/Ms Method for Multiple Residues/Contaminants In Bovine Meat - Hajrulai-Musliu, Zehra; Uzunov, Risto; Jovanov, Stefan; Jankuloski, Dean; Stojkovski, Velimir; Pendovski, Lazo; Sasanya, James Jacob (Research Square, 2020)
Abstract A multi-class and multi-residue/contaminant method for the determination of veterinary drug and pesticide residues and mycotoxins in bovine meat has been developed and validated. The veterinary drug residues/contaminants included antimicrobials, anabolic hormones, lactones, β-agonists, mycotoxins, and pesticides. Isotopic labeled internal standards were included to compensate residual matrix effects. The calibrators used in the method demonstrated linearity with the coefficient of correlation (R2) > 0.98. The decision limit (CCα) values were in the range from 0.067 to 2103.84 μg/kg, while the range for detection capability (CCβ) was from 0.083 to 2482.13 μg/kg. The limit of detection (LOD) and limit of quantification (LOQ) were in the range from 0.059 to 291.36 μg/kg, and 0.081 to 328.13 μg/kg, respectively. The recovery of analytes ranged from 61.28 % to 116.20 %. The intra-day coefficient of variation (CV) was from 0.97 to 25.93 % and the inter-day CV was 2.30-34.04 %. The method has been used for the determination of 49 residues/contaminants in bovine meat.